2020
DOI: 10.1007/s00424-020-02451-9
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous recovery, time course, and circadian influence on habituation of the cardiovascular responses to repeated restraint stress in rats

Abstract: We investigated the spontaneous recovery, time course, and the influence of the time of day on the habituation of the cardiovascular responses with repeated exposure to restraint stress in male rats. Habituation of the corticosterone response to repeated restraint stress was also evaluated. The circulating corticosterone response decreased during both the stress and recovery periods of the tenth session of restraint. Habituation of the cardiovascular responses was identified as a faster return to baseline valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…For restraint stress, animals were kept for 60 min into a cylindrical plastic tube, as previously described ( Alves et al, 2010 , 2014 ). Animals were subjected to only one restraint session to avoid the habituation process ( Benini et al, 2019 ; Santos et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…For restraint stress, animals were kept for 60 min into a cylindrical plastic tube, as previously described ( Alves et al, 2010 , 2014 ). Animals were subjected to only one restraint session to avoid the habituation process ( Benini et al, 2019 ; Santos et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The animals were maintained for 30 min into the restraint tube (Gouveia et al, 2016;Barretto-de-Souza et al, 2018b). Each animal was submitted to a single session of stress to avoid habituation (Benini et al, 2019(Benini et al, , 2020Santos et al, 2020).…”
Section: Restraint Stressmentioning
confidence: 99%
“…For example, human subjects who repeated a stressful task exhibited attenuated cardiovascular reactivity and improved task performance 30 . A recent study in rats demonstrated that exposure to repeated restrain stress results in a clear habituation of both the HPA (hypothalamus-pituitary-adrenal axis, one of the main biological response pathways for stress) and cardiovascular response 31 . Such studies have led to the idea of “stress inoculation”, i.e., that exposure to measured stress may result in higher resilience toward later stresses 32 .…”
Section: Discussionmentioning
confidence: 99%